The Conference Noise Control 98 - ENGEL, Zbigniew W. (Archives of Acoustics, 1999)
The 11-th International Conference on Protection Against Noise named Noise Control 98 was held in Krynica on June 2-4, 1998. The conference was arranged by the Acoustic Committee of the Polish Academy of Sciences, the Polish Acoustic Society, the Department of Mechanics and Vibroacoustics of the University of Mining and Metallurgy, the Central Institute for Labour Protection and the Building Research Institute.